1997
DOI: 10.1302/0301-620x.79b4.0790553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Local Recurrence on the Prognosis of Soft-Tissue Sarcomas

Abstract: We have investigated the significance of local recurrence on survival in 173 patients with localised soft-tissue sarcomas of the limbs and of the trunk.The overall survival rates at five and ten years were 75.2% and 68.0%, respectively. After definitive surgery at our hospitals, there was local recurrence in 25 patients (14.5%). After inadequate operations elsewhere, there was a higher incidence of late local recurrence (28.3%), in comparison with those with primary tumours treated by us (9.0%), or patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
3
14
0
3
Order By: Relevance
“…Local recurrence (data not shown) was significantly associated with overall survival irrespective of clinical presentation of recurrence (at the time of initial presentation or following definitive surgery). However, Ueda et al 1 specifically distinguished factors related to presentation of local recurrence in the analysis of the prognostic impact of local disease failure, concluding that neither initially presenting nor post-definitive resection local recurrence significantly influences survival after resection of localized soft-tissue sarcomas in multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Local recurrence (data not shown) was significantly associated with overall survival irrespective of clinical presentation of recurrence (at the time of initial presentation or following definitive surgery). However, Ueda et al 1 specifically distinguished factors related to presentation of local recurrence in the analysis of the prognostic impact of local disease failure, concluding that neither initially presenting nor post-definitive resection local recurrence significantly influences survival after resection of localized soft-tissue sarcomas in multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This study was conducted within the musculoskeletal oncology units at McGill University Health Centre and Maisonneuve-Rosemont Hospital. [7,10,13,16,25,27,28,30]. Local recurrences resulting from inadequate treatment have reported better prognosis than those occurring after a more comprehensive approach, with 5-year survival figures of 50% and 32%, respectively [1,11,22].…”
Section: Introductionmentioning
confidence: 99%
“…Ueda et al 22 found that the local recurrence rate was higher in patients who received unplanned surgery than those who received successful primary wide excision. 23 Fiore et al 14 analyzed 597 consecutive patients with primary STSs. Of the 597 patients, 318 were referred after unplanned surgery and the remaining 279 patients underwent primary resection.…”
Section: Impact Of Unplanned Surgery On Prognosismentioning
confidence: 99%